The Effectiveness of the Moving to Emptiness Technique on Clients Who Need Help During the COVID-19 Pandemic: A Real-World Study - Yanqiang Tao; Yi Chen; Wen Zhou; Lihui Lai; Tianjun Liu (Frontiers Media S.A., 2022)
With Western therapeutic techniques prevailing in Chinese therapies, some techniques that include Chinese traditional cultural features are required since some cultural factors are not considered in the Western method. Our study introduced a new technique, the moving to emptiness technique (MET), which combines Western structural progress and core factors of Chinese culture. Seventeen therapists treated 107 clients with the MET. Clients reported their target symptoms initially, and therapists helped them transfer invisible symptoms to perceivable stuff and remove their jarring stuff using the psychological emptiness area. At the end of the consultations, we found that MET could eliminate symptoms immediately. By grouping target symptoms according to their frequency, the results showed that clients in the high-frequency symptom group had higher rehabilitation rates than those in the low-frequency symptom group. Additionally, the results of the bereavement group were better than those of the non-bereavement group, indicating that the MET can significantly alleviate clients' target symptoms. In future studies, the replication and stability of the MET can be assessed by integrating questionnaires, experimental designs, and neurological equipment.